Targeted mass spectrometry for the analysis of nutritive modulation of catalase and heme oxygenase-1 expression - Zänglein, Nina; Tucher, Joanna; Pischetsrieder, Monika (Journal of Proteomics, 2015)
Comprehensive physiological food assessment requires recording of activity profiles. To elucidate the nutritive regulation of antioxidant enzymes, a generally applicable targeted MS method was established for the expression analysis of catalase and then adapted to heme oxygenase-1. Before tryptic digestion, target proteins were prefractionated by off-gel IEF of stimulated and control cell lysate. Targeted proteome analysis was achieved by LC coupled with scheduled selected reaction monitoring MS using 2 proteotypic peptides per protein and 3-4 transitions per peptide. Relative quantification was performed by stable isotope labeling by amino acids in cell culture (SILAC). The assay showed good correlation with results by Western blot. Linearity, precision, and sensitivity were even improved (LC/SRM vs. Western blot: 3 vs. 1 orders of magnitude, RSD 3.7-13.7% vs. 18.4%, LOD 0.2 vs. 1.6μg/mL). The developed method indicated that coffee does not modulate catalase expression in macrophages (T7cat 103±22%, T17cat 103±16%, p>0.05 vs. control), but leads to a highly significant increase of heme oxygenase-1 expression (T15Ho-1 420±24%, T22Ho-1 364±37%, p<0.001 vs. control, p>0.05 T15Ho-1 vs. T22Ho-1). In regard to multiplex options of the method, targeted proteome analysis can be a valuable tool for the comprehensive analysis of cellular effects of food components. Biological significance: In the present study, targeted mass spectrometry was applied to determine the influence of food components on the expression of antioxidative enzymes. The results implicate that targeted proteomics may develop into a valuable tool in food science and nutrition to determine the physiological effects of nutrients. In contrast to conventional methods for expression analysis, targeted proteome analysis can be applied to monitor the effects of a food component on a broad range of cellular targets in parallel. Additionally, proteins or protein modifications can be addressed which elude immunochemical methods.
UnivIS-Import:2015-03-09:Pub.2015.nat.dchph.llmch.target
Keywords: Expression analysis; Food proteomics; Nutrition; Selected reaction monitoring; SILAC; Targeted mass spectrometry